Завдання та функції Державної митної служби України як суб’єкта протидії порушенням митних правил - Бухарєва, Ю. В.; Bukharieva, Yu. V. (Європейські перспективи. - 2024. - № 1. - С. 193-200, 2024)
У статті наголошено на тому, що Державна митна служба України відіграє надзвичайно важливу роль у забезпеченні митної безпеки, контролю за переміщенням товарів та сприянні розвитку міжнародних торговельних відносин. Відзначено необхідність системних реформ у законодавстві, яке регулює діяльність функції Державної митної служби України. Чіткі норми, відповідні міжнародним стандартам, мають важливе значення для покращення роботи служби. Визначено основні завдання та функції Державної митної служби України як суб’єкта протидії порушенням митних правил.

The article emphasizes that the State Customs Service of Ukraine plays an extremely important role in ensuring customs security, controlling the movement of goods and promoting the development of international trade relations. The need for systemic reforms in the legislation regulating the activities of the State Customs Service of Ukraine was noted. Clear rules in line with international standards are essential to improve service performance. It was emphasized that the automation of processes and the introduction of modern technologies into the work of the State Customs Service of Ukraine can signifi cantly increase its effi ciency and transparency, reduce the time for document processing. It is argued that reforms in the fi eld of customs activity require a comprehensive approach, which combines internal reforms, legislative changes, introduction of the latest technologies, strengthening of controls, cooperation with the public and cooperation at the international level. Only such an approach can ensure the creation of an effective and modern customs system that meets the modern challenges and needs of citizens and businesses of Ukraine. It was noted that the development and modernization of tools and technologies used by the State Customs Service of Ukraine is a key aspect for increasing its effi ciency. The introduction of modern information systems, analytical tools and automation of processes make it possible to detect violations more quickly and provide a prompt response to them. It is substantiated that the State Customs Service of Ukraine performs important tasks in the fi eld of control over customs rules, contributing to economic development and ensuring national security. Its effectiveness requires a combination of legal regulation, modern technologies and systematic cooperation with other authorities and international partners.

В статье подчеркивается, что Государственная таможенная служба Украины играет чрезвычайно важную роль в обеспечении таможенной безопасности, контроля за перемещением товаров и содействии развитию международных торговых отношений. Отмечена необходимость системных реформ в законодательстве, регулирующем деятельность функции Государственной таможенной службы Украины. Четкие нормы, соответствующие международным стандартам, имеют важное значение для улучшения работы службы. Определены основные задачи и функции Государственной таможенной службы Украины как субъекта противодействия нарушению таможенных правил.
Tasks and functions of the State Customs Service of Ukraine as a subject of combating violations of customs rules
Keywords: митна безпека; customs security; таможенная безопасность; Державна митна служба України; State Customs Service of Ukraine; Государственная таможенная служба Украины; функції; functions; функции; протидія порушенням митних правил; combating violations of customs rules; противодействие нарушениям таможенных правил